Pengaruh Progressif Muscle Relaxation (PMR) Terhadap Perubahan Kadar Glukosa Darah Pada Pasien Diabetes Melitus - Feny Marlena; Rusiandy Rusiandy; Rangga Riandyva (Jurnal Ilmu Keperawatan Indonesia, 2020)
The problem in this study is that there are still many changes in blood glucose levels in diabetes mellitus patients at the Lais Care Health Center. The aim of the study was to determine the effect of progressive muscle relaxation (PMR) on changes in blood glucose levels in diabetes mellitus patients at the Lais Care Health Center. The design of this study used a quasi-experimental design using a pre and post test design. The sample in this study amounted to 10 people. The data used are primary data and secondary data. The analysis used was univariate analysis and bivariate analysis, the statistical test used was the T test. The mean values of blood glucose before and after Progressive Muscle Relaxation (PMR) in Diabetes Mellitus patients were 211.00 mg / dl and 196.30 mg / dl. It was concluded that there was an effect of progressive muscle relaxation (PMR) on changes in blood glucose levels in Diabetes Mellitus patients (p = 0.000).